2008
DOI: 10.1007/s11556-008-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related slowing of movement as basal ganglia dysfunction

Abstract: Attributions of age-related deficits in motor function to structural changes are compromised once the elderly exhibit lower error rates. This is because performance decrements observed in older adults are attributed to inferred strategic preferences for accuracy over speed. To understand genuine age differences in performance, we argue in the following theoretical paper that research needs to resolve methodological shortcomings and account for them within theoretical models of aging. Accounts of aging need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(125 reference statements)
0
3
0
1
Order By: Relevance
“…For example, the FCs between DMN and FPN/attentional networks were increased in lifespan due to the dedifferentiation process of aging brain, occurrence of aging for late neurodevelopmental stages, and a compensatory for cognitive decline (Grady et al., 2016; Zhai & Li, 2019; Zonneveld et al., 2019). Meanwhile, the BGN was thought to be related to motor learning functions and the increased FC within BGN might suggest as a compensatory role of dysfunctions of motor learning, especially in Parkinson's disease‐related research (Lyman, Anguera, & Terman, 2011; Saling & Phillips, 2008). Furthermore, it was also found that the homologous basal ganglia circuitry was related to cognition and emotion (Saling & Phillips, 2008) and an increased FC within it might compensate high‐order cognition (Siman‐Tov, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the FCs between DMN and FPN/attentional networks were increased in lifespan due to the dedifferentiation process of aging brain, occurrence of aging for late neurodevelopmental stages, and a compensatory for cognitive decline (Grady et al., 2016; Zhai & Li, 2019; Zonneveld et al., 2019). Meanwhile, the BGN was thought to be related to motor learning functions and the increased FC within BGN might suggest as a compensatory role of dysfunctions of motor learning, especially in Parkinson's disease‐related research (Lyman, Anguera, & Terman, 2011; Saling & Phillips, 2008). Furthermore, it was also found that the homologous basal ganglia circuitry was related to cognition and emotion (Saling & Phillips, 2008) and an increased FC within it might compensate high‐order cognition (Siman‐Tov, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the BGN was thought to be related to motor learning functions and the increased FC within BGN might suggest as a compensatory role of dysfunctions of motor learning, especially in Parkinson's disease‐related research (Lyman, Anguera, & Terman, 2011; Saling & Phillips, 2008). Furthermore, it was also found that the homologous basal ganglia circuitry was related to cognition and emotion (Saling & Phillips, 2008) and an increased FC within it might compensate high‐order cognition (Siman‐Tov, 2016). In lifespan, the BGN might play a compensatory role to balance the dysfunction of other functional networks.…”
Section: Discussionmentioning
confidence: 99%
“…Age-related changes in the human brain’s functioning fundamentally affect the motor system, causing increased reaction time, low ability to control movements, and difficulties in learning new motor skills ( Frolov et al, 2020 ). The performance decrements observed in older adults are also attributed to inferred strategic preferences for accuracy over speed ( Saling and Phillips, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…本文提出了毕生常模生成器及基于 RFB 的预测方法,都属于深度学习模型,而深度学 习模型的参数设置决定了模型的收敛效果。从弱化参数影响的角度出发,本文未对 VAE 及 预测模型进行复杂的参数寻优,而是尽可能的采用经验设置,以其在保证预测效果的同时, 将重心放在毕生常模生成及解释上。一方面从生物医学的角度解释常模,一方面探索深度 学习的"黑箱"效应。 毕生常模整体呈现左偏侧化,语言加工偏向于大脑左半球,而自然刺激状态是通过观 看电影实现的,影片中存在的对白可能是导致常模呈现左偏侧性的原因之一。毕生常模的 连接模式主要集中于额叶、枕叶、颞叶及部分深部核团,既包含了静息态下脑自发活动显 著的默认模式网络所涉及脑区,也存在自然刺激状态下活动显著的视觉网络、运动网络、 听觉网络等。此外,有研究表明,儿童大脑发育过程中呈现出左偏侧化 [29] 。而毕生常模中 跨越左右脑的连接模式主要集中于岛盖部额下回-缘上回间、回直肌-尾状核间、海马-颞中 回间,涉及额顶网络、视觉网络、基底节网络及默认模式网络。毕生中功能连接降低的网 络涉及额顶网络,默认模式网络。随着年龄增长,感觉运动功能逐渐下降,而部分运动及 皮层下网络内的功能连接随着年龄的增加反而升高,可能由于运动功能随老化进程加深导 致的代偿作用 [30,31] 。额顶网络的功能涉及执行控制过程中协调其他功能网络的核心作用 [32] 。 缘上回位于颞叶外侧,其功能涉及不同的认知过程,包括视觉空间处理、语言理解和记忆 检索,可能影响"动作效应(Enactment effect)",是相关的重点核心结构 [33] 。而内侧额 上回被认为与高级认知功能,尤其是工作记忆有关,自然刺激范式也会引起相关工作记忆 的功能。这种左偏侧化及主要连接模式从大脑功能的角度证实了毕生常模的准确性。个体 差异连接模式主要集中于基底节网络与默认模式网络、额顶网络、视觉网络、感觉运动网 络之间及深部核团内部连接。通常,网络间的功能连接升高在毕生中反映了一种代偿机制, 常由于大脑晚期神经发育阶段的老化导致的认知功能下降的代偿 [34][35][36] 。而基底节网络一般 与运动学习功能相关,其内部变化可能在老化中起到运动学习功能障碍的代偿作用,常见 于帕金森病相关研究中 [37,38] ,同源基底节回路与认知、情绪相关。相关个体差异连接模式 的变动能够准确捕捉个体认知能力的差异,从而有效地预测年龄及流体智力、反应时等行 为评分。 在预测年龄阶段,个体 FC 需要结合毕生常模、个体差异模式重参数计算得到特征, 其计算过程由于存在服从均值为零标准差为一的高斯分布采样参与计算,因而每一个批次 训练的潜变量都会发生变化。这样的扰动能够有效地提升预测模型的泛化能力。预测结果 显示,年龄预测误差的变异程度随着年龄增加呈现先降后升的趋势,即年轻人、老年人变 化较大,中年人稳定,与发展人口相关研究所展示的结论一致 [39][40][41] 。在先前研究中 [42] With extensive attention to human brain health worldwide, researchers are devoted to discovering the development and aging mechanisms of individual brains to assess the degree of brain aging and cognitive ability. The rapid development of functional Magnetic Resonance Imaging (fMRI) has provided robust technical support for neuroscience research.…”
Section: 取特征。unclassified